Design de interfaces para visualização, exploração e análise de coleções fotográficas - Giannella, Júlia Rabetti (2020)
This research aims to investigate how and for whom data visualization enables both the signification and the discovery processes in photographic collections search systems and, for this, focuses on user-centered design solutions that assume the epistemological role of collec- tions as both the object and the means of analysis. Our attention is on collections maintai- ned by cultural institutions (museums, libraries, archives, institutes, etc.). Currently, we see a growing interest in framing collections as data, that is, based on the simultaneous perception of digital reproductions and their metadata. Within this approach, issues related to the field of Design and that concern the design of informational spaces for photographic collections arise. Since keyword search is the dominant — yet ungenerous — information seeking paradigm, as it withholds more than it provides, we believe that, considering aspects of cataloging, multidi- mensionality and scale in said collections, we can design a new kind of search system. This new system is based on visualization techniques and interactive functionalities that amplify explora- tion and analysis activities performed by the users. This thesis is conducted through a methodo- logical procedure that combines theoretical and practical research. The theoretical stage covers a literature review in the areas of Digital Humanities, Visualization, and Cultural Heritage, as well as the examination of existing solutions for image collection visualization. At the end of Chapter 1, we identify conceptual gaps and project opportunities that serve as focal issues for the interface design proposal of a new system: the Fotovis. The practice-led stage is conducted through a case study carried out at the Instituto Moreira Salles (IMS), an important institution in Brazil’s cultural landscape. From a collaboration that allowed access to a sample of pho- tographs for instantiating Fotovis, as well as a close cooperation with specialists, curators and less specialized audiences, it was possible to prototype Fotovis in a concrete use scenario. The prototype and its subsequent evaluation lead to results that serve as empirical evidence of the thesis and are relevant for Cultural Heritage institutions and for the field of Digital Humanities. The results are also valuable for disciplines of Interface Design, Information Visualization and, Human-Computer Interaction.